2001
DOI: 10.1089/152581601317210890
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Step Colony-Forming Unit Assay for Unseparated Mobilized Peripheral Blood, Cord Blood, and Bone Marrow

Abstract: The colony-forming unit (CFU) assay is exposed to a lot of variation, part of which is introduced by several enrichment strategies that are routinely performed before assessment of clonogenic capacity in mobilized peripheral blood (PB), bone marrow (BM), or cord blood (CB). We investigated the possibility to perform a single-step CFU assay by direct plating of PB, BM, or CB into CFU culture medium to obtain more reproducible results than after a standard Ficoll or lysis procedure. Direct plating implies the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…We investigated the causes of this difference, and we found a negative influence of RBC content in CB sample before cryopreservation on CFU counts. Other authors, also with a direct plating method, have found the negative influence of RBC content on CFU–GM growth if a concentration of greater than 0.02 × 10 9 per mL was present in the CFU medium 24 . We have not determined the concentration of RBCs in medium, and we have no explanation for these data.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We investigated the causes of this difference, and we found a negative influence of RBC content in CB sample before cryopreservation on CFU counts. Other authors, also with a direct plating method, have found the negative influence of RBC content on CFU–GM growth if a concentration of greater than 0.02 × 10 9 per mL was present in the CFU medium 24 . We have not determined the concentration of RBCs in medium, and we have no explanation for these data.…”
Section: Discussionmentioning
confidence: 70%
“…Other authors, also with a direct plating method, have found the negative influence of RBC content on CFU-GM growth if a concentration of greater than 0.02 ¥ 10 9 per mL was present in the CFU medium. 24 We have not determined the concentration of RBCs in medium, and we have no explanation for these data. A possible influence of HES in protecting HPCs during the cryopreservation process could explain these results.…”
Section: Discussionmentioning
confidence: 94%
“…2B). 19 Human umbilical cord blood (55-95 mL) was collected from placentas immediately after cesarean delivery, and MNCs were isolated, as described earlier (Fig. 2B).…”
Section: Protocol Bmentioning
confidence: 99%
“…Thus, when comparing a UCB product with high ATP and low CFC numbers to a UCB unit with low ATP and high CFC numbers, one might interpret this to mean that progenitors are more immature in the former than in the latter UCB unit. Although there are reports showing some level of success in minimizing the magnitude of variability associated with the CFC assay, [20][21][22][23] it has been difficult to standardize this method among laboratories for the purpose of measuring the functional potential of progenitors contained within UCB. This is probably because there are a number of possible sources of error contributing to assay variability, which include the use of different cytokines by different laboratories, sample preparation, the plating of cells into methylcellulose, and the subjective interpretation of the colony number and type as the final readout for the CFC assay.…”
Section: Discussionmentioning
confidence: 99%